Noises off! - Marshall, Frank; Bogdanovich, Peter (Touchstone Home Entertainment, 2004)
Noise off! is an outrageously funny look at the love, lies and deceit that take place behind the scenes as a group of ridiculously inept stage actors rehearse a Broadway-bound play! Just when members of this chaotic cast finally get their performances right - everything starts going wrong.